C-F-S-H crystal nucleus early strength agent for offshore wind power grouting material and preparation method of C-F-S-H crystal nucleus early strength agent
By introducing sodium polyacrylate and polyethylene glycol into C-F-S-H crystal core particles to form a mesh structure, the particle agglomeration problem is solved, and the early strength and durability of offshore wind power grouting materials are significantly improved, and the stability and performance of the material are improved. .
Patent Information
- Application Number
- CN202411259996.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
Existing C-F-S-H crystal core particles are prone to adsorption and agglomeration in offshore wind grouting materials, resulting in poor stability and affecting the early strength and durability of the material.
Soluble calcium salts, iron salts, silicates, sodium polyacrylate and polyethylene glycol are used as dispersants to form a network structure through cross-linking, reducing the heterogeneous charge and van der Waals force between particles, and improving the stability of the crystal nucleus. And fill gaps in the grout to improve density and corrosion resistance.
It significantly improves the early strength and mechanical properties of offshore wind power grouting materials at all ages, maintains durability, and has good long-term dispersion stability.
Smart Images

Figure CN119118560A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of crystal nucleus early strength agent preparation, and in particular relates to a CFSH crystal nucleus early strength agent for offshore wind power grouting material and a preparation method thereof. Background Art
[0002] Cement-based grouting materials are the preferred materials for industrial equipment installation, bolt anchoring, repair and reinforcement projects. With the rapid development of social economy, there are more and more super high-rise buildings, offshore oil platforms, offshore wind power projects, etc., and the performance requirements of grouting materials are getting higher and higher. Due to the particularity of offshore wind power projects, the grouting materials are not only required to have good fluidity and stability during the pumping stage, but also to have high strength and high durability in the marine environment after hardening.
[0003] Cement-based materials are multi-phase, multi-component, multi-scale anisotropic materials. The types of cement hydration products are numerous and complex. Calcium silicate hydrate is one of the main components, accounting for about 70% of the total hydration products. Calcium silicate hydrate (CSH) has an important influence on the strength of cement paste. The CSH produced in the hydration of ordinary cement is generally represented by xCaO-ySiO2-zH2O to express its material composition. CSH usually changes with time and environmental changes. It is a low-crystallinity, amorphous product.
[0004] Since the composition and structure of CSH nanocrystalline core are similar to those of CSH gel, they can serve as nucleation sites to promote the nucleation and growth of CSH gel, thereby improving the early strength development of cement-based materials. In cement-based materials containing mineral admixtures, due to the introduction of active elements of mineral admixtures such as aluminum, magnesium and iron, the main reaction product is transformed from CSH to C-(A / F / M)-SH (CaO-(Al2O3 / Fe2O3 / MgO)-SiO2-H2O).
[0005] In the existing technology, Fe3 is added during the synthesis of CSH / PCE. + , successfully synthesized a new type of CFSH / PCE (calcium-ferrite-silicate-hydrate / polycarboxylate ether) nanocomposite material. 3+ The addition of does not affect the concentration of free calcium in the CFSH / PCE suspension, and the morphology of the suspension is composed of irregular spherical and reticular gels. However, in practical applications, it is found that the synthesized CFSH (CaO-Fe2O3-SiO2-H2O) crystal core particles are prone to adsorption and agglomeration. Summary of the invention
[0006] Purpose of the invention: The technical problem to be solved by the present invention is to provide a CFSH crystal nucleus early strength agent and a preparation method thereof. The CFSH crystal nucleus early strength agent has good long-term dispersion stability, can significantly improve the mechanical properties and durability of offshore wind power grouting materials at all ages, especially can significantly improve the early strength of offshore wind power grouting materials, and has no adverse effect on its durability.
[0007] Technical solution: The present invention discloses a CFSH crystal nucleus early strength agent for offshore wind power grouting material, wherein the CFSH crystal nucleus early strength agent comprises the following raw materials: a soluble calcium salt, a soluble iron salt, a soluble silicate and a dispersant; the molar ratio of Ca to Si in the soluble calcium salt, the soluble iron salt and the soluble silicate is (0.8-1.2):1, and the molar ratio of iron to silicon is (0.01-0.05):1; and the dispersant is sodium polyacrylate and polyethylene glycol in a mass ratio of 1:(1-2).
[0008] The present invention introduces Fe3 + , synthesize CFSH crystal nuclei, and use a dispersant composed of sodium polyacrylate and polyethylene glycol in the preparation, sodium polyacrylate is dissolved in a system composed of soluble calcium salt, soluble iron salt, soluble silicate and water, and polyethylene glycol is added, and its terminal hydroxyl group is cross-linked with the carboxyl group of sodium polyacrylate to form a polymer with a network structure, and the CFSH crystal nucleus particles generated by the reaction of soluble calcium salt, soluble iron salt, soluble silicate and water are separated by the polymer with the network structure, which reduces the intermolecular interaction forces such as heterogeneous charges and van der Waals forces between CFSH crystal nucleus particles, reduces the agglomeration between particles, and improves the stability of the crystal nucleus. And the network structure polymer formed can fill the gaps between the grouting materials when applied to the grouting materials, thereby improving the density and anti-corrosion performance of the grouting materials.
[0009] Furthermore, the soluble calcium salt used in the CFSH crystal nucleus early strength agent of the present invention is calcium nitrate, calcium formate, calcium acetate, calcium bicarbonate or calcium gluconate.
[0010] Furthermore, the soluble iron salt used in the CFSH crystal nucleus early strength agent of the present invention is ferric nitrate, ferric sulfate or ferric chloride.
[0011] Furthermore, the soluble silicate used in the CFSH crystal nucleus early strength agent of the present invention is sodium fluorosilicate, sodium silicate, sodium metasilicate or potassium silicate.
[0012] Furthermore, the total mass ratio of the soluble calcium salt, soluble silicate and soluble iron salt used in the CFSH crystal nucleus early strength agent of the present invention to the mass ratio of the dispersant is 100:(1-5).
[0013] The method for preparing the CFSH crystal nucleus early strength agent of the present invention comprises the following steps:
[0014] (1) preparing a soluble calcium salt aqueous solution and a soluble silicate aqueous solution respectively, and adding a soluble iron salt to the soluble calcium salt aqueous solution to prepare a mixed solution;
[0015] (2) After the mixed solution and the soluble silicate aqueous solution are mixed, a sodium polyacrylate aqueous solution is added, followed by polyethylene glycol, the pH is adjusted to 11.0-13.4, and the mixture is stirred and reacted at 20-50° C. for 12-16 hours to obtain the CFSH crystal nucleus early strength agent.
[0016] Furthermore, in step (1) of the method for preparing the CFSH crystal nucleus early strength agent of the present invention, the concentration of the soluble calcium salt in the aqueous solution of the soluble calcium salt is 20-50%.
[0017] Furthermore, in step (1) of the method for preparing the CFSH crystal nucleus early strength agent of the present invention, the concentration of the soluble silicate in the soluble silicate aqueous solution is 10-30%.
[0018] Furthermore, in step (1) of the method for preparing the CFSH crystal nucleus early strength agent of the present invention, the concentration of the soluble iron salt in the mixed solution is 0.6-2%.
[0019] Furthermore, in step (2) of the method for preparing the CFSH crystal nucleus early strength agent of the present invention, the concentration of the sodium polyacrylate aqueous solution is 0.1-0.6%.
[0020] Beneficial effects: Compared with the prior art, the significant advantages of the present invention are: the CFSH nucleus early strength agent has good long-term dispersion stability, can significantly improve the mechanical properties and durability of offshore wind power grouting materials at all ages, especially can significantly improve the early strength of offshore wind power grouting materials, and has no adverse effect on its durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the XRD diagram of the CSH crystal nucleus early strengthening agent of Example 1 of the present invention;
[0022] Figure 2 These are the SEM and EDS images of the CFSH crystal nucleation early strength agent of Example 1 of the present invention. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be noted that the raw materials used in the present invention can all be purchased from the market.
[0024] Example 1
[0025] The raw materials of the CFSH crystal nucleus early strength agent used for offshore wind power grouting material in Example 1 are: calcium nitrate, ferric nitrate, sodium metasilicate, sodium polyacrylate and polyethylene glycol composite dispersant in a mass ratio of 1:1. Among them, the molar ratio of Ca to Si in calcium nitrate, ferric nitrate and sodium metasilicate is 1:1, and the molar ratio of iron to silicon is 0.03:1. The total mass ratio of calcium nitrate, ferric nitrate and sodium metasilicate to the mass ratio of dispersant is 100:3, the amount of dispersant added is 8.4g, and the amount of other raw materials added can be confirmed according to their respective corresponding relationships.
[0026] The preparation method of the CFSH crystal nucleation early strength agent of Example 1 comprises the following steps:
[0027] (1) preparing a calcium nitrate aqueous solution with a mass concentration of 40% and a sodium metasilicate aqueous solution with a mass concentration of 20%, respectively, and adding a soluble iron salt to the calcium nitrate aqueous solution to prepare a mixed solution with a ferric nitrate concentration of 1%;
[0028] (2) Prepare a sodium polyacrylate aqueous solution with a mass concentration of 0.3%.
[0029] (3) After the mixed solution and the sodium metasilicate aqueous solution are mixed, the sodium polyacrylate aqueous solution is added, and then polyethylene glycol is added, the pH is adjusted to 12.4±0.1, and the mixture is stirred and reacted at 35° C. for 14 hours to obtain the CFSH crystal nucleus early strength agent.
[0030] The crystal core prepared in Example 1 was subjected to a crystal core structure test with reference to CSH, and the obtained results are as follows: Figure 1 As shown, the corresponding particles with CSH crystal core structure were characterized by SEM and EDS, and the results obtained are as follows Figure 2 As shown. Figure 1 and Figure 2 It can be seen that the crystal nucleus prepared in the present invention meets the structural characteristics of the CSH crystal nucleus, and there is Fe in the crystal nucleus, which proves the formation of the CFSH crystal nucleus structure of the present invention.
[0031] Example 2
[0032] The raw materials of the CFSH crystal nucleation early strength agent for offshore wind power grouting material in Example 2 are: calcium formate, ferrous sulfate, sodium fluorosilicate, sodium polyacrylate and polyethylene glycol composite dispersant in a mass ratio of 1:1. Among them, the molar ratio of Ca to Si in calcium formate, ferrous sulfate and sodium fluorosilicate is 0.8:1, and the molar ratio of iron to silicon is 0.01:1. The total mass ratio of calcium formate, ferrous sulfate and sodium fluorosilicate to the mass ratio of the dispersant is 100:1, and the amount of the dispersant added is 8.4g. The amount of other raw materials added can be confirmed according to their respective corresponding relationships.
[0033] The preparation method of the CFSH crystal nucleation early strength agent of Example 2 comprises the following steps:
[0034] (1) preparing a calcium formate aqueous solution with a mass concentration of 20% and a sodium fluorosilicate aqueous solution with a mass concentration of 10%, respectively, and adding ferric sulfate to the calcium formate aqueous solution to prepare a mixed solution with a ferric sulfate concentration of 0.6%;
[0035] (2) Prepare a sodium polyacrylate aqueous solution with a mass concentration of 0.1%.
[0036] (3) After the mixed solution and the sodium fluorosilicate aqueous solution are mixed, the sodium polyacrylate aqueous solution is added, and then polyethylene glycol is added, the pH is adjusted to 11.0±0.1, and the mixture is stirred and reacted at 20° C. for 16 hours to obtain the CFSH crystal nucleus early strength agent.
[0037] Example 3
[0038] The raw materials of the CFSH crystal nucleation early strength agent used for offshore wind power grouting material in Example 3 are: calcium acetate, ferric chloride, potassium silicate, sodium polyacrylate and polyethylene glycol composite dispersant in a mass ratio of 1:2. Among them, the molar ratio of Ca to Si in calcium acetate, ferric chloride and potassium silicate is 1.2:1, and the molar ratio of iron to silicon is 0.05:1. The total mass ratio of calcium acetate, ferric chloride and potassium silicate to the mass ratio of dispersant is 100:5, and the amount of dispersant added is 8.4g. The amount of other raw materials added can be confirmed according to their respective corresponding relationships.
[0039] The preparation method of the CFSH crystal nucleus early strength agent of Example 3 comprises the following steps:
[0040] (1) preparing a calcium acetate aqueous solution with a mass concentration of 50% and a potassium silicate aqueous solution with a mass concentration of 30%, respectively, and adding ferric chloride to the calcium acetate aqueous solution to prepare a mixed solution with a ferric chloride concentration of 2%;
[0041] (2) Prepare a sodium polyacrylate aqueous solution with a mass concentration of 0.6%.
[0042] (3) After the mixed solution and the potassium silicate aqueous solution are mixed, the sodium polyacrylate aqueous solution is added, and then polyethylene glycol is added, the pH is adjusted to 13.4±0.1, and the mixture is stirred and reacted at 50° C. for 12 hours to obtain the CFSH crystal nucleus early strength agent.
[0043] Comparative Example 1
[0044] The basic steps are the same as those in Example 1, except that only sodium polyacrylate is used as the dispersant. The details are as follows:
[0045] The raw materials of the CFSH crystal nucleus early strength agent used in the comparative example 1 for offshore wind power grouting material are: calcium nitrate, ferric nitrate, sodium metasilicate, and sodium polyacrylate dispersant. Among them, the molar ratio of Ca to Si in calcium nitrate, ferric nitrate, and sodium metasilicate is 1:1, and the molar ratio of iron to silicon is 0.03:1. The total mass ratio of calcium nitrate, ferric nitrate, and sodium metasilicate to the mass ratio of the dispersant is 100:3, and the amount of the dispersant added is 8.4g. The amounts of other raw materials added can be confirmed according to their respective corresponding relationships.
[0046] The preparation method of the CFSH crystal nucleus early strength agent of comparative example 1 comprises the following steps:
[0047] (1) preparing a calcium nitrate aqueous solution with a mass concentration of 40% and a sodium metasilicate aqueous solution with a mass concentration of 20%, respectively, and adding a soluble iron salt to the calcium nitrate aqueous solution to prepare a mixed solution with a ferric nitrate concentration of 1%;
[0048] (2) Prepare a sodium polyacrylate aqueous solution with a mass concentration of 0.3%.
[0049] (3) After the mixed solution and the sodium metasilicate aqueous solution are mixed, the sodium polyacrylate aqueous solution is added, the pH is adjusted to 12.4±0.1, and the mixture is stirred and reacted at 35° C. for 14 hours to obtain the CFSH crystal nucleus early strength agent.
[0050] Performance Testing
[0051] In order to test the effect of the CFSH crystal nucleus early strength agent prepared in the embodiment in the offshore wind power grouting material, cement, sand, steel slag, defoaming agent, water, expansion agent and water reducing agent are mixed according to the proportions in Table 1 to form offshore wind power grouting material. The early strength agent adopts the CFSH crystal nucleus early strength agent prepared by the present invention, and two curing ages of 12h and 1d are set respectively. The specific proportions are shown in Table 1 below, and the results obtained are shown in Table 2 below.
[0052] Table 1 Offshore wind power grouting material mix ratio
[0053] Cement / g Steel slag / g Water / g Sand / g Early strength agent (%) Water reducing agent (%) Bulking agent (%) Defoaming agent (%) 600 150 192 750 0.8 0.5 0.03 0.3
[0054] Table 2 Fluidity and compressive strength of offshore wind power grouting materials with different iron-silicon ratios
[0055]
[0056]
Claims
1. A CFSH crystal nucleation early strength agent for offshore wind power grouting materials, It is characterized in that The CFSH crystal nucleus early strength agent comprises the following raw materials: a soluble calcium salt, a soluble iron salt, a soluble silicate and a dispersant; the molar ratio of Ca to Si in the soluble calcium salt, the soluble iron salt and the soluble silicate is (0.8-1.2):1, and the molar ratio of iron to silicon is (0.01-0.05):1; and the dispersant is sodium polyacrylate and polyethylene glycol in a mass ratio of 1:(1-2).
2. The CFSH crystal nucleation early strength agent for offshore wind power grouting material according to claim 1, It is characterized in that The soluble calcium salt is calcium nitrate, calcium formate, calcium acetate, calcium bicarbonate or calcium gluconate.
3. The CFSH crystal nucleation early strength agent for offshore wind power grouting material according to claim 1, It is characterized in that The soluble iron salt is ferric nitrate, ferric sulfate or ferric chloride.
4. The CFSH crystal nucleation early strength agent for offshore wind power grouting material according to claim 1, It is characterized in that The soluble silicate is sodium fluorosilicate, sodium silicate, sodium metasilicate or potassium silicate.
5. The CFSH crystal nucleation early strength agent for offshore wind power grouting material according to claim 1, It is characterized in that The total mass ratio of the soluble calcium salt, the soluble silicate and the soluble iron salt to the mass ratio of the dispersant is 100:(1-5).
6. A method for preparing the CFSH crystal nucleus early strength agent according to claim 1, It is characterized in that The steps include: (1) preparing a soluble calcium salt aqueous solution and a soluble silicate aqueous solution respectively, and adding a soluble iron salt to the soluble calcium salt aqueous solution to prepare a mixed solution; (2) After the mixed solution and the soluble silicate aqueous solution are mixed, a sodium polyacrylate aqueous solution is added, followed by polyethylene glycol, the pH is adjusted to 11.0-13.4, and the mixture is stirred and reacted at 20-50° C. for 12-16 hours to obtain the CFSH crystal nucleus early strength agent.
7. The method for preparing a CFSH crystal nucleus early strength agent according to claim 6, It is characterized in that In step (1), the concentration of the soluble calcium salt in the aqueous solution of the soluble calcium salt is 20-50%.
8. The method for preparing CFSH crystal nucleation early strengthening agent according to claim 6, It is characterized in that In step (1), the concentration of soluble silicate in the soluble silicate aqueous solution is 10-30%.
9. The method for preparing a CFSH crystal nucleus early strength agent according to claim 6, It is characterized in that In step (1), the concentration of soluble iron salt in the mixed solution is 0.6-2%.
10. The method for preparing CFSH crystal nucleation early strength agent according to claim 6, It is characterized in that In step (2), the mass concentration of the sodium polyacrylate aqueous solution is 0.1-0.6%.
